Can caffeine intake improve neuromuscular and technical-tactical performance during judo matches? - Athayde, M. S. da S.; Lima Kons, R.; Detanico, D. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to verify the effect of caffeine intake on blood lactate concentrations and neuromuscular and technical-tactical performance during simulated judo matches. Fourteen male judo athletes received capsules containing caffeine or placebo and were evaluated in both conditions. Before the baseline and 1 hour after the caffeine/placebo intake, athletes performed the countermovement jump (CMJ) test, handgrip strength, judogi grip strength test (JGST), and blood samples were collected. Subsequently, the athletes were submitted to three 5-minute matches with 15-minute intervals. All neuromuscular tests were performed and blood samples were taken during the matches' intervals. Significant interaction between condition and time (p = 0.01) was found for blood lactate concentrations. No interaction between condition and time was verified for CMJ performance (p > 0.05), handgrip strength (p > 0.05), JGST performance (p = 0.32), and number of attacks (p = 0.97). However, for all variables, a significant decrease was observed throughout time (p = 0.05). According to clinical results (magnitude-based inference), we identified that post-match 2 and post-match 3 showed higher effect (most likely positive effect) regarding delta caffeine—placebo than other moments (pre-match and post-match 1) for blood lactate. Caffeine increased the estimated glycolytic contribution over the matches; however, it did not induce improvements in neuromuscular performance or number of attacks.